Recalculating the Orbit of Î±-Centauri AB - Suryadi Siregar; Hanindyo Kuncarayakti (Institut Teknologi Bandung, 2007)
The two main components of the closest star system, Î± Centauri AB (RA 14h39m, Dec -60o50, J2000.0) is indubitablyone of the most studied visual double stars. This paper presents the results of our recalculation of orbital and physicalparameters of the system using Thiele-van den Bos method, based on observational data from year 1900 to 2002.Despite some significant discrepancies, in general our results confirmed previous results of orbital parameterdeterminations using different method.